Staged Endovascular Treatment for Symptomatic Occlusion Originating From the Intracranial Vertebral Arteries in the Early Non-acute Stage - Duan, Hongzhou; Chen, Li; Shen, Shengli; Zhang, Yang; Li, Chunwei; Yi, Zhiqiang; Wang, Yingjin; Zhang, Jiayong; Li, Liang (Frontiers in Neurology, 2021)
Background: The ideal treatment for patients who survive from acute vertebrobasilar artery occlusion but develop aggressive ischemic events despite maximal medical therapy in the early nonacute stage is unknown. This paper reports the technical feasibility and outcome of staged endovascular treatment in a series of such patients with symptomatic intracranial vertebral artery occlusion. Methods: Ten consecutive patients who presented with aggressive ischemic events in the early nonacute stage of intracranial vertebral artery occlusion from Jan 2015 to Nov 2020 were retrospectively reviewed. Among them, eight male and two female patients with a mean age of 66.7 years developed aggressive ischemic events, and the NIHSS score was elevated by a median of 7 points despite medical therapy. All patients received staged endovascular treatment 4-21 days from onset, at an average of 11 days. The strategy of staged treatment was as follows: first, a microwire was passed through the portion of the occlusion, which was then dilated with balloon inflation to maintain the perfusion above TICI grade 2b. Then, with the use of antiplatelet drugs, the residual intravascular thrombus was gradually eliminated by the continuous perfusion and an activated fibrinolytic system, leaving the residual stenosis. A second stage of angioplasty with stent implantation was subsequently performed if residual stenosis was ≥50%. The NIHSS scores and mRS scores were compared between pre- and post-endovascular treatment groups and in the follow-up period. Results: Technical success was achieved in 9 patients who received staged endovascular treatment (perforation occurred in one patient during the first stage). The NIHSS scores were significantly improved, with a median score 7 points lower on discharge compared with the scores for the most severe status. Favorable outcomes with mRS score≤2 were achieved in 7 and 9 patients at the 3-month follow-up and the latest follow-up, respectively, which was better than the preoperative status. Conclusion Staged endovascular treatment might be a safe, efficient, and viable option in carefully selected patients with symptomatic intracranial vertebral artery occlusion in the early nonacute stage. However, this needs to be confirmed by further investigation, preferably in a large, controlled setting.